How Are The Science Process Skills of Prospective Science Teacher Students: Studies in Inorganic Chemistry and Gender - Ramlawati (Universitas Pendidikan Ganesha, 2024)
Prospective teacher students must be able to design practicums so that the learning process is meaningful. The skills that students develop in carrying out scientific discoveries, namely applying concepts, rules, and characteristics that exist in science, are called science process skills (SPS). Therefore, in building students' knowledge, students must have process skills in teaching so they can teach effectively and must have a good understanding of concepts and strong process skills. This research aims to describe the SPS of prospective science education teacher students through inorganic chemistry courses after going through learning with the discovery learning model. This research uses a quantitative approach with a pre-experimental design one-shot case study research method. The research results show that student SPS as a whole is in the high category with an average percentage of 59.71%. SPS analysis in classes A, B, and C, respectively, has an average percentage of 58.23%, 62.66%, and 58.24% in the high category. SPS analysis based on gender shows that the respective percentage of male students is 53.89% with the medium category for women and 59.81% for the high category.